Enhancement of Mixing Performance of Non-Newtonian Fluids using Curving and Grooving of Microchannels - S. Baheri Islami; Marzieh Khezerloo (Journal of Applied Fluid Mechanics, 2017)
In this study, a numerical investigation was performed on the mixing of non-Newtonian power-law fluids in curved micromixers with power-law indices between 0.49 and 1 and Reynolds numbers between 0.1-300. The properties of water and CMC solution were used for simulation of Newtonian and non-Newtonian fluid flows, respectively. The effects of grooves embedded on the bottom wall of micromixers and geometrical parameters such as depth and angle of grooves on mixing performance were examined. The mixing of non-Newtonian fluids using this kind of micromixers has not been studied before. Eventually, using of inclined grooves with 30° inclination angle was studied. Open source CFD code of OpenFOAM was utilized to simulate the mixing process. The results showed that the grooves caused chaotic advection and improved the mixing performance but had no significant effect on dimensionless pressure drop. Also, the grooves with 30◦ angle showed better mixing index for all values of power-law indices.